2012
DOI: 10.1152/ajplung.00387.2011
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptor A2b on hematopoietic cells mediates LPS-induced migration of PMNs into the lung interstitium

Abstract: Konrad FM, Witte E, Vollmer I, Stark S, Reutershan J. Adenosine receptor A2b on hematopoietic cells mediates LPS-induced migration of PMNs into the lung interstitium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 57 publications
5
43
0
Order By: Relevance
“…A 2B R signaling has been reported to be broadly antiinflammatory in several models of acute lung injury; in particular, A 2B R deficiency is associated with increased lung inflammation after challenge with bleomycin, LPS, ischemia-reperfusion, and ventilator-associated lung injury (29,(36)(37)(38). The reported mechanisms of these effects have varied markedly between these models and have included alteration of leukocyte traffic, reduction in vascular permeability mediated by bone marrow-derived cells, and attenuation of the neutrophil oxidative burst (14,37,38); on the other hand, work has shown A 2B R expression on bone marrow-derived cells to paradoxically enhance neutrophil migration to the lung interstitium in response to LPS (39). We speculate that the reported differences in the mechanisms of A 2B R effects in these models reflect differences in dynamics of production and degradation of adenosine, and differences in the number of adenosine-responsive cells as well as their adenosine receptor repertoire in the context of different injuries.…”
Section: Discussionmentioning
confidence: 99%
“…A 2B R signaling has been reported to be broadly antiinflammatory in several models of acute lung injury; in particular, A 2B R deficiency is associated with increased lung inflammation after challenge with bleomycin, LPS, ischemia-reperfusion, and ventilator-associated lung injury (29,(36)(37)(38). The reported mechanisms of these effects have varied markedly between these models and have included alteration of leukocyte traffic, reduction in vascular permeability mediated by bone marrow-derived cells, and attenuation of the neutrophil oxidative burst (14,37,38); on the other hand, work has shown A 2B R expression on bone marrow-derived cells to paradoxically enhance neutrophil migration to the lung interstitium in response to LPS (39). We speculate that the reported differences in the mechanisms of A 2B R effects in these models reflect differences in dynamics of production and degradation of adenosine, and differences in the number of adenosine-responsive cells as well as their adenosine receptor repertoire in the context of different injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are marginated in the alveolar capillaries in infectious or noninfectious ALI, and this process involves engagement of chemokine-receptor interactions (267) and of different families of endothelial and epithelial adhesion molecules, such as JAMs (junctional adhesion molecules), ICAM-1 (intercellular adhesion molecule-1), PECAM-1 (platelet endothelial cell adhesion molecule-1), and VCAM-1 (vascular adhesion molecule-1), which are upregulated upon release of inflammatory mediators like TNF-␣ (16,93,131). In addition, leukocyte-expressed adenosine receptor A(2b) and eicosanoid expression are attributed a role in pulmonary neutrophil recruitment in LPS-induced ALI or after Pseudomonas aeruginosa infection in mice (102,124). Once recruited into the alveolar compartment, neutrophils release proteases or neutrophil extracellular traps composed of chromatin and antimicrobial agents, which may cause endo-or epithelial injury (163,201).…”
Section: Immune Cells and Inflammatory Signaling Pathways In Alimentioning
confidence: 99%
“…In addition, lung edema is prominent in seawater induced ALI because high osmotic seawater pull water through vascular endothelial cells and alveolar epithelial cells [4], [5]. It has been reported that increased alveolar epithelial and pulmonary microvascular endothelial permeability trigger the transmigration of inflammatory cells such as neutrophils and the formation of edema fluid [6]. Accordingly, inhibition of inflammation and lung tissue barrier permeability may be propitious to the promotion of seawater aspiration-induced ALI.…”
Section: Introductionmentioning
confidence: 99%